Supplemental Feeding and Food Plots for Bobwhite Quail - William M. Giuliano; James F. Selph; Robert Hoffman; Brandon J. Schad (EDIS)
WEC-224, a 3-page illustrated fact sheet by William M. Giuliano, James F. Selph, Robert Hoffman, and Brandon J. Schad, describes considerations for a successful artificial feeding programs for bobwhite quail, including spreading feed and planting food plots. Includes a table of common food plot plants for bobwhites in Florida. Published by the UF Department of Wildlife Ecology and Conservation, June 2007.